The institutionalization of an online reporting system - Wangmo, Karma (Technical Centre for Agricultural and Rural Cooperation, 2018)
To improve progress reporting within the Commercial Agriculture and Resilient Livelihoods Enhancement Programme (CARLEP), which works to enhance market engagement and climate resilience of farmers in Bhutan, the project introduced a standardised online reporting system. The system is helping to reduce the workload of the field and implementation staff, as well as helping increase the transparency of the programme.